Detection of Partial G6PD Deficiency using OSMMR2000-D Kit with Hb Normalization - Azma, RZ; Zubaidah, MS; Azlin, I; Hafiza, A; Nurasyikin, Y; Hidayati, SN; Farisah, ARN; Hamidah, HN; Ainoon, O (Univ Kebangsaan Malaysia, Fac Medicine, 2024)
Indexed by WOS